Wybrane aspekty partycypacji oraz upodmiotowienia pracowników - Kolasińska, Anna; Gach, Daniel (Some aspects of the participation and workers empowerment, 2005)
This article presents a few selected aspects of participation and workers empowerment. In the first part of the article authors presents the ideas and assumptions of these managements conceptions. In the next section authors presents the methods and rules of implement empowerment. In the last part of the publication authors describes the threats of the participation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 563-572